2014
DOI: 10.1002/ajpa.22649
|View full text |Cite
|
Sign up to set email alerts
|

Human–wildlife conflict: Proximate predictors of aggression between humans and rhesus macaques in India

Abstract: Macaques live in close contact with humans across South and Southeast Asia, and direct interaction is frequent. Aggressive contact is a concern in many locations, particularly among populations of rhesus and longtail macaques that co-inhabit urbanized cities and towns with humans. We investigated the proximate factors influencing the occurrence of macaque aggression toward humans as well as human aggression toward macaques to determine the extent to which human behavior elicits macaque aggression and vice vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 33 publications
0
20
0
1
Order By: Relevance
“…Bonnet macaques are found in sub-tropical to dry deciduous or scrub-forest environments in Southern India (Sinha, 2013), where they also tend to inhabit anthropogenic landscapes (Radhakrishna & Sinha, 2011;Singh & Rao, 2004;Sinha & Mukhopadhyay, 2013). Research on other macaque species has revealed that individual attributes like sex and dominance rank may influence variation in animals' tendencies to interact with humans (rhesus macaques: Beisner et al, 2015; longtailed macaques: Fuentes & Gamerl, 2005) and their grooming strategies (Henzi & Barrett, 1999). In addition, affiliative behaviors may also be impacted by both group-specific attributes (e.g., group size, sex-ratio, home-range size) as these may determine the number and spatial spread of potentially available partners (Berman & Thierry, 2010;Lehmann et al, 2007), and by seasonal differences in climatic conditions which influence ecological factors such as food distribution or human presence/activity and thereby primate socioecology and behavior (Korstjens & Hillyer, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Bonnet macaques are found in sub-tropical to dry deciduous or scrub-forest environments in Southern India (Sinha, 2013), where they also tend to inhabit anthropogenic landscapes (Radhakrishna & Sinha, 2011;Singh & Rao, 2004;Sinha & Mukhopadhyay, 2013). Research on other macaque species has revealed that individual attributes like sex and dominance rank may influence variation in animals' tendencies to interact with humans (rhesus macaques: Beisner et al, 2015; longtailed macaques: Fuentes & Gamerl, 2005) and their grooming strategies (Henzi & Barrett, 1999). In addition, affiliative behaviors may also be impacted by both group-specific attributes (e.g., group size, sex-ratio, home-range size) as these may determine the number and spatial spread of potentially available partners (Berman & Thierry, 2010;Lehmann et al, 2007), and by seasonal differences in climatic conditions which influence ecological factors such as food distribution or human presence/activity and thereby primate socioecology and behavior (Korstjens & Hillyer, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Among many applications, such methods could be used to document situations where primates are in conflict with people in species ranging from chimpanzees (Pan troglodytes) [26] to macaques (Macaca mulatta) [27] allowing us to quantify the occurrence of such events and their spatial-temporal dynamics. One of the most high-profile non-human primate-human conflict occurs with people and baboons in the Cape Peninsula, South Africa, with baboons raiding bins, properties or taking food directly from people themselves daily [28].…”
Section: Introductionmentioning
confidence: 99%
“…Here we test whether direct interactions with humans either constrain animals' activity budgets (time constraints hypothesis) or free up the time they can allocate to resting and social interactions (free time hypothesis) in an urban-dwelling population of rhesus macaques. Rhesus macaques inhabit a variety of interfaces, from agricultural areas to cities and temples, resulting in a close proximity between macaques and humans (Chauhan & Pirta, 2010a;Southwick & Siddiqi, 2011;Beisner et al, 2015). To date, studies have shown that such close proximity leads to frequent interactions between the two species, which can take both potentially negative (e.g., mutual aggression) and positive (e.g., humans provisioning the macaques) forms (Chauhan & Pirta, 2010a, b;Beisner et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Rhesus macaques inhabit a variety of interfaces, from agricultural areas to cities and temples, resulting in a close proximity between macaques and humans (Chauhan & Pirta, 2010a;Southwick & Siddiqi, 2011;Beisner et al, 2015). To date, studies have shown that such close proximity leads to frequent interactions between the two species, which can take both potentially negative (e.g., mutual aggression) and positive (e.g., humans provisioning the macaques) forms (Chauhan & Pirta, 2010a, b;Beisner et al, 2015). However, little is known about whether and how such interactions with humans may impact macaque activity budgets, including affiliative social behaviours like grooming, despite well-documented evidence that affiliative social behaviours are associated with critical health and fitness benefits in group-living animals (Silk et al, 2003).…”
Section: Introductionmentioning
confidence: 99%